AGILITY PERFORMANCE ON EMPLOYEES AFFECTED BY TERMINATION - Kumalasari, Heny; Finda, Perdana Fiara; Talumingan, Geovani Beckam (AIBPM Publisher, 2022)
This article aims to determine the conditions of employees affected by layoffs at a garment company and able to survive during the Covid pandemic -19 by looking at the opportunities that exist. Garment companies carry out layoff policies due to the sluggish economy due to the Covid-19 pandemic. This is important to discuss because during Covid-19 the number of layoffs (Terminations of Employment) at the Garment factory increased but by taking advantage of the opportunities there were employees affected by layoffs were able to build SMEs. This study uses a qualitative approach with literature reviews, interviews, and focus group discussions (FGD) with the owners and managers of these SMEs and interviews were conducted on October 7, 2022. The results of this study show that employees are affected by layoffs are able to survive the Covid-19 pandemic. 19 by looking at the strengths, weaknesses, opportunities and threats. The employee saw an opportunity by establishing the SMEs in the fashion sector, especially women's accessories.